Genistein-mediated inhibition of glycosaminoglycan synthesis, which corrects storage in cells of patients suffering from mucopolysaccharidoses, acts by influencing an epidermal growth factor-dependent pathway - Jakóbkiewicz-Banecka, Joanna (BioMed Central, 2009)
BACKGROUND: Mucopolysaccharidoses (MPS) are inherited metabolic disorders caused by mutations leading to dysfunction of one of enzymes involved in degradation of glycosaminoglycans (GAGs). Due to their impaired degradation, GAGs accumulate in cells of patients, which results in dysfunction of tissues and organs. Substrate reduction therapy is one of potential treatment of these diseases. It was demonstrated previously that genistein (4', 5, 7-trihydroxyisoflavone) inhibits synthesis and reduces levels of GAGs in cultures of fibroblasts of MPS patients. Recent pilot clinical study indicated that such a therapy may be effective in MPS III (Sanfilippo syndrome). METHODS: To learn on details of the molecular mechanism of genistein-mediated inhibition of GAG synthesis, efficiency of this process was studied by measuring of incorporation of labeled sulfate, storage of GAGs in lysosomes was estimated by using electron microscopic techniques, and efficiency of phosphorylation of epidermal growth factor (EGF) receptor was determined by using an ELISA-based assay with fluorogenic substrates. RESULTS: Effects of genistein on inhibition of GAG synthesis and accumulation in fibroblasts from patients suffering from various MPS types were abolished in the presence of an excess of EGF, and were partially reversed by an increased concentration of genistein. No such effects were observed when an excess of 17β-estradiol was used instead of EGF. Moreover, EGF-mediated stimulation of phsophorylation of the EGF receptor was impaired in the presence of genistein in both wild-type and MPS fibroblasts. CONCLUSION: The results presented in this report indicate that the mechanism of genistein-mediated inhibition of GAG synthesis operates through epidermal growth factor (EGF)-dependent pathway.